2016
DOI: 10.1080/13854046.2016.1183049
|View full text |Cite
|
Sign up to set email alerts
|

The profession of neuropsychology in Spain: results of a national survey

Abstract: The field of neuropsychology in Spain is young and rapidly growing. There is a need to regulate professional neuropsychology, improve graduate curricula, enhance existing clinical training, develop professional certification programs, validate and create normative data for existing neuropsychological tests, and create new, culturally relevant instruments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
42
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 22 publications
0
42
0
4
Order By: Relevance
“…In Latin American countries and in Spain, this test is among the 10 most utilized neuropsychological tests by clinical neuropsychologists during their professional practice (Arango-Lasprilla, Stevens, Morlett-Paredes, Ardila, & Rivera, 2016;Olabarrieta-Landa et al, 2016). However, in spite of its great use, there are currently very few studies on validation and standardization of this test for Spanishspeakers.…”
Section: Discussionmentioning
confidence: 99%
“…In Latin American countries and in Spain, this test is among the 10 most utilized neuropsychological tests by clinical neuropsychologists during their professional practice (Arango-Lasprilla, Stevens, Morlett-Paredes, Ardila, & Rivera, 2016;Olabarrieta-Landa et al, 2016). However, in spite of its great use, there are currently very few studies on validation and standardization of this test for Spanishspeakers.…”
Section: Discussionmentioning
confidence: 99%
“…These children and adolescents are referred by teachers, school psychologists, and/or pediatricians who suspect potential learning or intellectual disabilities Olabarrieta-Landa et al, 2016). However, in Latin America, and Spain there is paucity of measurement research with regards to neuropsychological instruments, particularly those applicable to children Olabarrieta-Landa et al, 2016).…”
mentioning
confidence: 99%
“…A survey of Latin American and Spanish neuropsychologists, many of whom provided services to children, found that more than 50%, ranging from 49.0% to 62.0% depending on country, reported that lack of normative data for their regions was one of the major problems they encountered in providing neuropsychological evaluations. They reported resorting to use of normative data from other countries or using raw scores to interpret test results Olabarrieta-Landa et al, 2016). …”
mentioning
confidence: 99%
See 2 more Smart Citations